2017
DOI: 10.1016/j.jvolgeores.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Thallium isotopes as tracers of recycled materials in subduction zones: Review and new data for lavas from Tonga-Kermadec and Central America

Abstract: -Sediment is actively being subducted in every convergent margin worldwide. 18Yet, geochemical data for arc lavas from several subduction zones, such as Northern Tonga and 19 Costa Rica have revealed either attenuated or limited evidence for sediment in their mantle 20 source regions. Here we use thallium (Tl) isotopes to trace slab components in lavas from the 21 Tonga-Kermadec and Central American arcs. In general, both arcs display Tl isotope data that 22 are most compatible with addition of sediment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 108 publications
1
41
1
Order By: Relevance
“…Figure 1: Literature compilation of Tl concentrations and Tl stable isotopes (ɛ 205 Tl) for terrestrial and major marine sediments and reservoirs. (a -d) FeMn deposits (Rehkämper et al, 2002), (e) mantle (Nielsen et al, 2006b), (f) low temperature altered ocean crust (Nielsen et al, 2006a), (g -j) volcaniclastics/radiolarian and claystone/pelagic clays (Prytulak et al, 2013 andNielsen et al, 2017b), (j) diatom-bearing sediments (Nielsen et al, 2016), (k -l) river water and loess averages (Nielsen et al, 2005), (m) continental crust average (Nielsen et al, 2017a)., (n) soils (Kersten et al, 2014), and laterite values measured in this study. Where average ranges specified ɛ 205 Tl ± 1SD are reported.…”
Section: Figure Captionsmentioning
confidence: 69%
“…Figure 1: Literature compilation of Tl concentrations and Tl stable isotopes (ɛ 205 Tl) for terrestrial and major marine sediments and reservoirs. (a -d) FeMn deposits (Rehkämper et al, 2002), (e) mantle (Nielsen et al, 2006b), (f) low temperature altered ocean crust (Nielsen et al, 2006a), (g -j) volcaniclastics/radiolarian and claystone/pelagic clays (Prytulak et al, 2013 andNielsen et al, 2017b), (j) diatom-bearing sediments (Nielsen et al, 2016), (k -l) river water and loess averages (Nielsen et al, 2005), (m) continental crust average (Nielsen et al, 2017a)., (n) soils (Kersten et al, 2014), and laterite values measured in this study. Where average ranges specified ɛ 205 Tl ± 1SD are reported.…”
Section: Figure Captionsmentioning
confidence: 69%
“…In various environments, thallium is assumed to substitute potassium in secondary minerals (e.g. Nielsen et al, 2006Nielsen et al, , 2017Prytulak et al, 2017). For instance, in illite, K + takes place as counter ion on the negative surface charges and is strongly bounded to the structure in the interlayer space (Meunier, 2003).…”
Section: Thallium Sorption Behaviormentioning
confidence: 99%
“…Prytulak et al () did not find evidence of fluid mobile behavior of Tl in the Mariana arc, while Jenner et al () found positive Tl enrichments (relative to Ce and Pr) from some Lau back‐arc lavas and Nielsen et al () found Tl strongly partitions into the fluid phase at Mariana forearc. Recent Tl isotopic work indicates that the Tl budget of arc lavas are dominated by Tl from pelagic clays from a sediment mélange (Nielsen et al, , ; Shu et al, ). Jenner et al () also found correlated enrichments of As, Tl, Pb, and Bi in backarc lavas from the Manus Basin, which were interpreted by Jenner () as evidence of fluid enrichment of As, Tl, Pb, Sb, and Bi to arc crust.…”
Section: Discussionmentioning
confidence: 99%